Detection of vancomycin resistance enterococci in poultry and clinical samples and their resistance genes by multiplex PCR - Nasir, Nur Syafiqah Mohamad (2021)
Vancomycin resistance enterococci (VRE) has emerged as an important nosocomial pathogen that specializes in biofilm formation which contributes to their virulence and antibiotic resistance. VRE’s origin is unknown, but the emergence is believed to be associated with the overuse of antibiotic glycopeptides of avoparcin as a growth promoter in animal husbandry. This research was carried out to determine the prevalence of VRE and their resistance genes in poultry and to determine the resistance genes in archived clinical VRE. A total of 300 broiler’s cloaca swab samples (Gallus gallus domesticus) were collected after commercial poultry farms were identified and consented by the owners for sampling, while 38 of the archived VRE isolates were retrieved from various clinical samples from the Department of Medical Microbiology between 2016 and 2019. Broiler’s cloaca swab samples were taken using a sterile cotton swab and kept in an enriched broth. Enterococcus spp. were identified using morphological and biochemical testing, and an antibiotic susceptibility test was used to screen for vancomycin resistance. Following that, a multiplex PCR assay was optimized to simultaneously identify vancomycin resistance genes (vanA, vanB, vanC, and vanD) in poultry and clinical isolates. A total of 97 Enterococcus were obtained from 300 broiler’s cloaca swab samples. The isolates were identified Enterococcus casseliflavus (n=69/97; 71.1%) and Enterococcus gallinarum (n=28/97; 28.9%) by phenotypic and genotypic method. Among all the Enterococcus isolated from broiler’s cloaca swab samples, none of them were found to exhibit resistant to vancomycin.Isolates demonstrated 100% susceptibility to teicoplanin and tigecycline. Of all, 2/97 (2.1%) were exhibit resistance to high-level gentamicin. Whereas 48/97 (49.5%) were observed to be resistant to ampicillin, and 28/97 (28.9%) were resistant to penicillin. Interestingly, among the two species isolated, 18.6% (n=18/97) of it were resistant to linezolid. Despite no VRE was found in broiler farms in this study, persistence of VRE was detected in clinical setting. All the archived clinical VRE samples were found to possess a vanA gene, which has been linked to high-level vancomycin resistance. Preventing and controlling the spread of vancomycin resistance will require coordinated and concerted efforts from all involved hospital departments to reduce the persistence and transmission of VRE. New identified linezolid resistant Enterococcus (LRE) in this study causes an alarming problem to the animal husbandry as well as to the healthcare setting worldwide. This could result in possibly untreatable and severe enterococcal infections. Even more worrying, the spread of LRE to geographical regions that these resistant was previously unreported, potentially lead to global health threat. Therefore, antimicrobial surveillance in poultry husbandry is dimly necessary to prevent wide spread of multidrug-resistant organism.